How Does Risk-based Deposit Insurance Premium Affect Bank Risk Taking? Islamic Bank vis a vis Conventional Bank - Syed Abdullah, Sharifah Adlina (Journal of Technology Management and Business, 2020)
Central banks across the world implemented deposit insurance system as a major risk management practice in the post Global Financial Crisis (2007/2008) period. This study provides insights on the efficacy of deposit insurance policy in the Malaysian market where Islamic and conventional banking co-exist. Given that Islamic banking principles inherently limits bank risk taking ability, the study findings clearly identify the pertinent role of risk-based deposit insurance premium on mitigating potential increase bank risk in the post-financial crisis period. Using Malaysian banks data for the period 2002-2010, this study finds that Islamic banks have lower risk appetite than conventional banks. Most importantly, after the introduction of deposit insurance system, insolvency and operational risk increase mainly for conventional banks owing to inadequate premium. This calls for policymakers to carefully consider design features for an effective risk-based DI system that is risk-premium sensitive to ensure financial stability. Other policy implications include that the risk-based deposit insurance premium would prevent regulatory arbitrage, while Shariah compliance principles prevent the Islamic banks from adjusting their risk after the introduction of a deposit insurance system. Worth mentioning is the institution of an early warning mechanism policy as well as formal cooperation in information sharing protocols among policymakers, regulators and deposit insurance organisations to minimise operational risk in banks.